MORFOMETRI BURUNG WERIS Gallirallus philippensis dan BURUNG WERIS Gallirallus torquatus DI KOTA KOTAMOBAGU SULAWESI UTARA - Koyong, Stewart S; Wungouw, H R; Lambey, L; Laatung, S (ZOOTEC, 2014)
ABSTRACT Mandar bird ( Gallirallus ) or in Minahasa called with less weris bird has long been known by the people of North Sulawesi , Minahasa and especially the City of Kotamobagu. Is a bird in the family Rallidae family of birds that have a small to medium body size. General habitat of this bird is close river swamp or lake . Weris birds usually breed in thrive densely vegetated areas by Rusila (1994 ) . Identify the problem at least some information about morphometric characteristics some species of weris bird. In North Sulawesi city of Kotamobagu the purpose of this study was to obtain data morphometric characteristics of weris birds in the city of Kotamobagu. The expected benefits of the research , provide information about morphometric charaeteristics of weris birds , which is useful in the breeding process . Based on the results of research conducted in the City of Kotamobagu Bolaang Mongondo North Sulawesi , found 2 different types of weris birds that Gallirallus philippensis and Gallirallus torquatus . Of the two types of birds have different characters that can be seen from the outside or exterior appearance , and also can be seen from the size where Gallirallus philippensis have a smaller size compared to Gallirallus torquatus. . Keywords : bird weris , Morfomertri . Â